Pengaruh Motivasi Kerja Terhadap Organizational Citizenship Behavior Dan Kinerja Pegawai - Sri Agustin Permata Sari (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2021)
Purpose- This study aims to provide an empirical explanation of the effect of work motivation on organizational citizenship behavior and employee performance. Design/Methodology/Approach- The research method used is descriptive-quantitative. The population of all employees of Education Office of Palangka Raya City found 116 people with a sample consisting of 90 respondents with simple random sampling technique. Analyzed with SmartPLS 3.2.9 software. Finding- Showes that work motivation has a positive and significant effect on organizational citizenship behavior and on employee performance in the Education Office of Palangka Raya City.